2007
DOI: 10.1016/j.jacc.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Additional Prognostic Value of Coronary Flow Reserve in Diabetic and Nondiabetic Patients With Negative Dipyridamole Stress Echocardiography by Wall Motion Criteria

Abstract: Coronary flow reserve provides independent prognostic information in diabetic and nondiabetic patients with known or suspected coronary artery disease and negative dipyridamole stress echocardiography. In particular, a normal CFR off therapy is associated with better and similar survival in the 2 populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 52 publications
3
110
0
5
Order By: Relevance
“…It has been repeatedly reported that hyperglycemia is associated with increased stiffness of large vessels including aorta. Its compliance plays an important role in the coronary artery blood flow modulation, the myocardial workload capacity, and therefore also in the global exercise capacity (Kingwell 2002;Cortigiani et al 2007). As well, impaired exercise capacity in type 2 diabetes is associated not only with anthropometrical parameters, such as age, sex or BMI, but also with left ventricle dysfunction and impairment of cardiac autonomic regulation (Fang et al 2005;Sargin et al 2005;Kasahara et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly reported that hyperglycemia is associated with increased stiffness of large vessels including aorta. Its compliance plays an important role in the coronary artery blood flow modulation, the myocardial workload capacity, and therefore also in the global exercise capacity (Kingwell 2002;Cortigiani et al 2007). As well, impaired exercise capacity in type 2 diabetes is associated not only with anthropometrical parameters, such as age, sex or BMI, but also with left ventricle dysfunction and impairment of cardiac autonomic regulation (Fang et al 2005;Sargin et al 2005;Kasahara et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Night-shift work disrupts the normal biological and/or social diurnal rhythms, which are factors in cardiovascular disease, 1,2 as well as in a widening variety of other chronic diseases, including glucose intolerance, 3,4 hypertension 5,6 and depression. 7,8 Endothelium function, which is strongly associated with the onset and development of cardiovascular disease and its risk factors, [9][10][11] has been shown to be impaired after night-shift work. 12 There is a need for therapeutic options to alleviate the negative impact of working night shifts on the health of medical personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic role of echocardiography-derived CFR is widely examined in patients with suspected or known CAD [2][3][4][7][8][9][16][17][18][19][20][21][22][23][24][25]. CFR has a prognostic significance on cardiovascular outcome not only in patients with significant CAD [16], but also in subjects with intermediate (50 to 75%) LAD stenosis [17,18] or angiographically normal or near-normal coronary arteries [4,8,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, diabetes mellitus (DM) and CFR have been found to have a complementary prognostic role for the prediction of cardiovascular events in patients with and without coronary artery disease (CAD) [2]. Moreover, CFR provides independent prognostic information in diabetic and nondiabetic patients with known or suspected CAD and negative dipyridamole stress echocardiography [3]. The prognostic impact of CFR on survival was found even in a general population with normal or near-tonormal coronary arteries [4].…”
Section: Introductionmentioning
confidence: 99%